Korelasi Antar Sub Pokok Bahasan Termokimia Pada Siswa Kelas XI MIPA SMA Negeri Palangka Raya Tahun Ajaran 2018/2019 - Novitasari Novitasari (Jurnal Ilmiah Kanderang Tingang, 2021)
This study aims to describe the correlation between the sub-subjects of thermochemistry based on the value of the correlation coefficient and the correlation between sub-subjects of thermochemistry based on the average value (mean) of the test results. This research is a descriptive research that uses a quantitative approach and is included in the type of correlational research. The subjects in this study were students of class XI MIPA SMA Negeri 1 Palangka Raya, SMA Negeri 2 Palangka Raya, and SMA Negeri 4 Palangka Raya for the 2018/2019 academic year with a total of 514 students. The data used in the form of data on students' ability to the concept of thermochemistry which is indicated by the achievement of indicators. The data was collected through a test using multiple choice questions (TKT) as many as 32 questions. Student ability test data in the form of answers were analyzed using correlation and descriptive methods. The results showed that the order of presentation of the thermochemical sub-topic based on the correlation coefficient values, namely: (1) bond energy (ENIKA), (2) heat and reaction enthalpy change (KPER), (3) thermochemical equation (PETER), (4) standard enthalpy changes for various reactions (PESBR), and (5) determination of reaction enthalpy changes (PENER). KPER), (2) thermochemical equation (PETER), (3) determination of reaction enthalpy change (PENER), (4) standard enthalpy change for various reactions (PESBR), and (5) bond energy (ENIKA). The order of presentation above is different from the order based on the syllabus.